Action of disinfectant solutions on adaptive capacity and virulence factors of the Candida spp. biofilms formed on acrylic resin - Badaró, Mauricio Malheiros; Bueno, Frank Lucarini; Makrakis, Lais Ranieri; Araújo, Camila Borba; Oliveira, Viviane de Cássia; Macedo, Ana Paula; Paranhos, Helena de Freitas Oliveira; Watanabe, Evandro; Silva-Lovato, Cláudia Helena (Journal of Applied Oral Science, 2021)
Understanding the behavior of Candida spp. when exposed to denture disinfectants is essential to optimize their effectiveness. Changes in the virulence factors may cause increased resistance of Candida spp. to disinfectant agents. Objective: To evaluate the microbial load, cellular metabolism, hydrolytic enzyme production, hyphae formation, live cell and biofilm quantification of Candida albicans, Candida tropicalis and Candida glabrata after exposure to disinfectant solutions. Methodology: Simple biofilms were grown on heat-polymerized acrylic resin specimens, and divided into groups according to solutions/strains: distilled water (control); 0.25% sodium hypochlorite (NaOCl 0.25% ); 10% Ricinus communis (RC 10%); and 0.5% Chloramine T (CT 0.5%). The virulence factors were evaluated using the CFU count (microbial load), XTT method (cell metabolism), epifluorescence microscopy (biofilm removal and live or dead cells adhered), protease and phospholipase production and hyphae formation. Data were analyzed (α=0.05) by one-way ANOVA/ Tukey post hoc test, Kruskal-Wallis test and Wilcoxon test. Results: NaOCl 0.25% was the most effective solution. CT 0.5% reduced the number of CFUs more than RC 10% and the control. RC 10% was effective only against C. glabrata. RC 10% and CT 0.5% decreased the cellular metabolism of C. albicans and C. glabrata. Enzyme production was not affected. Hyphal growth in the RC 10% and CT 0.5% groups was similar to that of the control. CT 0.5% was better than RC 10% against C. albicans and C. tropicalis when measuring the total amount of biofilm and number of living cells. For C. glabrata, CT 0.5% was equal to RC 10% in the maintenance of living cells; RC 10% was superior for biofilm removal. Conclusions: The CT 0.5% achieved better results than those of Ricinus communis at 10%, favoring the creation of specific products for dentures. Adjustments in the formulations of RC 10% are necessary due to efficacy against C. glabrata. The NaOCl 0.25% is the most effective and could be suitable for use as a positive control.